4-Alkyl-3-azidomethyl-2-ethoxy-2,5-dihydro-5H-1,2-oxaphosphole 2-Oxides: Synthesis and 1,3-Cycloaddition - Brel, Valery K.; Alekseychuk, Ekaterina P.; Artyushin, Oleg I.; Anikina, Lada V. (Synthesis, 2021)
Starting from phosphorylated allenes, a three-steps synthesis of a new class of organic azides with a 1,2-oxaphospholene carbon skeleton has been developed. The series of obtained 4-alkyl-3-azidomethyl-2-ethoxy-2,5-dihydro-5H-1,2-oxaphosphole 2-oxides were utilized in the 1,3-cycloaddition with alkyl 2-[1-(propyn-2-yl)-1H-indol-3-yl]-2-oxoacetates for the synthesis of conjugates, which are potentially active cytostatics.
Keywords: allenes; azides; 1,2-oxaphosphole 2-oxides; 1,2,3-triazoles; indolylglyoxyl derivatives